Gambaran tingkat kepuasan pemakai gigi tiruan sebagian lepasan dengan kuesioner PDA-ID GTSL - Agustin Gozali, Ivana; Teguh, Sharren (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Tooth loss is a condition that is influenced by various factors, including age. With age, the incidence of tooth loss also increases. The prevalence of individuals with partial tooth loss is quite high in Indonesia. Treatment with removable partial denture (RPD) is important to rehabilitate and replace the functions of missing teeth. The Indonesian version of the Patient’s Denture Assessment (PDA-ID) questionnaire will be modified, then validity and reliability tests were carried out in this study so it can be used to evaluate patient satisfaction with RPDs. Aim: To evaluate the level of patient satisfaction with RPD, which was measured using a modified Indonesian version of the PDA questionnaire. Methods: The type of this research is descriptive observational with a cross sectional research design. This research is conducted by distributing a modified PDA-ID questionnaire to 43 respondents who had received treatment for maxillary and mandibular RPDs by a dentist, and domiciled in South Tangerang City. Results: 88,4% respondents is satisfied with the removable partial denture they are using after being measured by a modified PDA-ID questionnaire (PDA-ID GTSL). Conclusion: The majority of respondents is satisfied with their RPD. The PDA-ID GTSL questionnaire is a valid and reliable measuring tool to evaluate the satisfaction of patients with RPDs.